2007
DOI: 10.1111/j.1742-7843.2007.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Steroidal Anti‐Inflammatory Drugs, Cyclooxygenase‐2 and the Bone Healing Process

Abstract: Traditional non-steroidal anti-inflammatory drugs (NSAID) and selective cyclooxygenase-2 (COX-2) inhibitors are widely used in the treatment of pain, including bone fracture pain and orthopaedic post-operative pain. The gastrointestinal and cardiovascular adverse effects of NSAIDs are acknowledged, but their effects on bone are less widely known.Prostaglandins play an important role in the regulation of osteoblast and osteoclast functions, and inhibition of prostaglandin production retards bone formation. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(106 citation statements)
references
References 61 publications
0
89
0
12
Order By: Relevance
“…Another NSAID used in HO prevention, celecoxib, has been shown in other populations to be as effective an antiinflammatory medication as indomethacin with fewer gastrointestinal adverse effects. 39 Hence, it is reasonable to assume that it may be as effective in patients with SCI and should be further studied in this population. Radiotherapy for prevention of HO after SCI also acts through the inhibition of mesenchymal cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Another NSAID used in HO prevention, celecoxib, has been shown in other populations to be as effective an antiinflammatory medication as indomethacin with fewer gastrointestinal adverse effects. 39 Hence, it is reasonable to assume that it may be as effective in patients with SCI and should be further studied in this population. Radiotherapy for prevention of HO after SCI also acts through the inhibition of mesenchymal cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are often observed in the healing process of adult fractures irrespective of the use of cryotherapy. It has been reported that osteoclasts in the healing process of fractures are absorbed in the damaged bones to rebuild new bones [14]. Therefore, it is possible that the spreading out of the fracture site on the radiographic image in this case results in osteoclast production to remove the damaged bone, which does not correlate to the patient's symptoms, especially pain.…”
Section: Discussionmentioning
confidence: 83%
“…Laut [2]. Prospektive randomisierte klinische Studien zu Knochenheilungsstö-rungen nach tNSAR und speziell COX-2-Hemmer-Gabe nach Operationen fehlen bisher [8].…”
Section: Der Fallunclassified